Anomalous Branching Pattern of the Popliteal Artery (PA): A Case Report - Sumalatha, Suhani (JCDR Research and Publications (P) Limited, 2014)
The Popliteal Artery (PA), which is the continuation of the Femoral artery, crosses the popliteal fossa at the distal border of popliteus; it divides into the Anterior and Posterior Tibial arteries. The Posterior Tibial Artery (PTA) divides into terminal branches proximal to popliteus, in which case the Anterior Tibial Artery (ATA) sometimes descends anterior to the muscle. Either the Anterior tibial or the PTA may be reduced or increased in size. The dorsalis pedis artery (DPA) is the continuation of the ATA, distal to the ankle. It passes to the proximal end of the first intermetatarsal space, to complete the plantar arch, and provides the first plantar metatarsal artery. In the present case the PA bifurcates into two terminal branches at a higher level than the normal. The ATA was hypo plastic and entered the anterior crural region in front of the popliteus muscle and finally terminated above the knee joint. Further the PTA was also hypo plastic giving off a hyperplastic PL which pierced the interosseous membrane and on entering the dorsum of the foot, it prolonged as the DPA. The rest of the PTA continued its course distally and divided into its usual branches, the medial and lateral planter arteries. Awareness of these variations in the vascular branching patterns of the lower limb, acts as a guide during femero distal bypass grafting procedures and surgical and percutaneous vascular reconstructions.